High-Performance Hydroxyapatite Scaffold Combined with Selenium and Reduced Graphene Oxide for Bone Regeneration Applications - Y. Beygi-Khosrowshahi; S. Zakhireh (Iranian Journal of Chemical Engineering)
Bone tissue engineering requires approaches to provide a suppression/promotion environment for the bone growth. Scaffold biomaterials have profound regulatory effects on the functionality of mesenchymal stem cells (MSCs). In the present study, the three-component bioceramic of selenium/reduced graphene oxide/hydroxyapatite (Se/RGO/HA) was developed and its performance to repair bone defects was compared to that of HA. The Se/RGO/HA nanocomposite scaffold was synthesized using the chemical bath technique, characterized by the X-ray diffraction spectra, field emission scanning electron microscopy, energy dispersion X-ray spectrometery, and Fourier transform infrared spectroscopy analyses. Human adipose-derived MSCs (hAD-MSCs) were used to investigate the in-vitro osteogenic properties of the Se/RGO/HA scaffold. The effect of the combined scaffold on the cell proliferation was analyzed by the MTT assay. Cell adhesion behaviors were evaluated using the optical microscopy and SEM. The osteogenic properties of the Se/RGO/HA scaffold were examined by the measurement of the alkaline phosphatase (ALP) activity and western blotting technique. The hAD-MSCs proliferation for HA and the Se/RGO/HA nanocomposite were 2 ± 0.1 and 1.1 ± 0.05 respectively. The Se/RGO/HA nanocomposite had cytotoxic effects on the KHOS-240S cancer cells. Additionally, good cell attachment and osteoblast-like morphology were characterized on the designed scaffold. The ALP activity and mineralization potential of cells seeded on Se/RGO/HA were higher than those seeded on HA. The Osteocalsin protein for Se/RGO/HA and HA were 64 ± 1 and 12 ± 0.1 respectively. Furthermore, the expression of Osteocalcin, a bone-specific protein, was synergistically increased by the incorporation of Se and RGO into HA. In conclusion, the presence of RGO inside Se could significantly increase the positive effects of HA on the osteogenic potential of hAD-MSCs.